Prepaid Water Consumption System Via RFID Controlled by Microcontroller - Muankhaw, Theerapol; Ngaemngam, Surin; Thongchan, Chatchai; Chaiprachiad, Jittinat (Frontiers in Engineering Innovation Research, 2024)
This research presents a prepaid water consumption system via RFID controlled by a microcontroller with a notification through an LED lamp for dormitories or apartments. The objective of this study is to facilitate dormitory or apartment owners no need to record water consumption in individual rooms and reduce issues related to tenants facing fines due to late payment of water bills. The system is composed of two parts: the prepaid machine and the water consumption control machine. The operation of the system uses RFID cards as an intermediary for communication between the prepaid machine and the water consumption control machine. It is required to top up money on the RFID card and place this card on the water consumption control machine to turn on the system and to use the water for any purpose. The efficiency of the proposed system was tested by testing the operation of the whole system starting from topping-up money into RFID cards, placing the cards on the water consumption control machine, and turning off the system when the system has no money. The experimental results found that the system can be used correctly. Moreover, the efficiency of the system was tested by comparing water consumption through the proposed water consumption control system with a general water meter by testing it 5 times. The experimental results found that the water consumption from the proposed system was equal to the water consumption from a general water meter.